Effectiveness of Alternative Statistical Approaches in Testing the Significance of the Null Hypothesis to Improve Reliability in Marketing Research - Wiguna, Ardhitya Alam; Ardi, Aditya Nizar Al; Saadillah, Dinu; Hakim, Lukman; Pinandita, Candra Pramula (Journal of Business Management, 2024)
This study examines the effectiveness of various alternative statistical approaches in testing the null hypothesis's significance to improve marketing research's reliability. Conventional methods such as p-value are often misunderstood and have limitations in interpreting the results of the analysis. Therefore, this study compares several alternative approaches, including Bayesian inference, bootstrap resampling, and false discovery rate, to improve the validity and repeatability of marketing research results. By using a simulation-based quantitative approach and a survey of marketing academics and practitioners, the findings of this study show that alternative methods can provide more informative results than conventional techniques. The implications of this study contribute to strengthening marketing research methodologies to be more accurate and reliable.